Lipid Rafts, Sphingolipids, and Ergosterol in Yeast Vacuole Fusion and Maturation - Hurst, Logan R.; Fratti, Rutilio A. (Frontiers in Cell and Developmental Biology, 2020)
The Saccharomyces cerevisiae lysosome-like vacuole is a useful model for studying membrane fusion events and organelle maturation processes utilized by all eukaryotes. The vacuolar membrane is capable of forming micrometer and nanometer scale domains that can be visualized using microscopic techniques and segregate into regions with surprisingly distinct lipid and protein compositions. These lipid raft domains are liquid-ordered (Lo) like regions that are rich in sphingolipids, phospholipids with saturated acyl chains, and ergosterol. Recent studies have shown that these lipid rafts contain an enrichment of many different proteins that function in essential activities such as nutrient transport, organelle contact, membrane trafficking, and homotypic fusion, suggesting that they are biologically relevant regions within the vacuole membrane. Here, we discuss recent developments and the current understanding of sphingolipid and ergosterol function at the vacuole, the composition and function of lipid rafts at this organelle and how the distinct lipid and protein composition of these regions facilitates the biological processes outlined above.